Harmonic Performance in Hybrid AC-DC Microgrid Connected Bidirectional Converter with LCL Filter - Hasti Afianti; Ahmadi Ahmadi; Saidah Saidah; Richa Watiasih; Bambang Purwahyudi (JEECS (Journal of Electrical Engineering and Computer Sciences), 2026)
This paper presents the harmonic performance of a grid-connected hybrid AC-DC microgrid. Using solar power as a source in the DC microgrid and the grid in the AC microgrid eliminates the need for energy storage. Solar power generation is known to be intermittent, requiring a power supply to meet the load demand in the DC microgrid. Therefore, a converter that can operate as both an inverter and a rectifier is required. One way to address this issue is to use a bidirectional AC-DC converter (BC). To perform its function, this converter requires a filter to reduce the switching frequency ripple current injected into the grid. Among the available options, the LCL filter is widely recognized as the most effective solution for suppressing switching frequency harmonics. In this study, the performance of the LCL filter will be analyzed through simulations using MATLAB/Simulink. The results show that the bidirectional AC-DC converter designed with the LCL filter effectively suppresses resonances occurring at the converter output in rectifier or inverter mode., the voltage in the AC microgrid remained stable, the THD stayed below 5%, and the system frequency was well maintained. However, during the standby period, when the power transfer in both the DC and AC microgrids is zero, the THD on the grid remains high, up to 200%.